A niclosamide–tobramycin hybrid adjuvant potentiates cefiderocol against P. aeruginosa. Issue 9 (9th August 2021) - Berry, Liam; Brizuela, Marc; Jackson, Gregory; Schweizer, Frank
Abstract : A niclosamide-tobramycin hybrid was shown to synergize with cefiderocol, a recently approved siderophore cephalosporin, against multidrug-resistant Pseudomonas aeruginosa . Abstract : There is an urgent need for new therapies to overcome antimicrobial resistance (AMR) especially against Gram-negative bacilli (GNB). Multicomponent therapy combining antibiotics with enhancer molecules known as adjuvants is an emerging strategy to combat AMR. We have previously reported tobramycin-based adjuvants which are able to potentiate various antibiotics. In order to expand the repertoire of tobramycin hybrid adjuvants, a new hybrid containing niclosamide, an FDA approved anthelmintic which has recently demonstrated a variety of interesting biological effects, was synthesized. It was found that this conjugate can potentiate several antibiotics against multidrug-resistant GNB, including the recently approved siderophore cephalosporin cefiderocol. 8 μg ml −1 of the niclosamide–tobramycin hybrid in combination therapy against a pandrug-resistant strain of P. aeruginosa was able to lower the cefiderocol MIC 32-fold, from 8 μg ml −1 to 0.25 μg ml −1 in iron-rich media where siderophore uptake is reduced. These results indicate that a niclosamide–tobramycin hybrid adjuvant can serve to potentiate a newly approved antibiotic.